PENGARUH HARGA SUKUK NEGARA RITEL SR021, YIELD IMBAL HASIL SUKUK DAN MINAT INVESTASI TERHADAP PERMINTAAN SUKUK NEGARA RITEL SR021 DI INDONESIA - Muhamad Rizkyansyah; Ridwansyah Ridwansyah; Dinda Fali Rifan (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2026)
This study aims to analyze the effect of the price of Retail Government Sukuk SR021, sukuk yield, and investment interest on the demand for Retail Government Sukuk SR021 in Indonesia. The method used is multiple linear regression analysis with the assistance of Eviews 13 software. The results show that sukuk prices have a negative effect on demand, meaning that an increase in price tends to reduce investors' interest in purchasing sukuk. Conversely, yield has a positive effect on demand, indicating that the rate of return is a primary consideration for investors in making investment decisions. Meanwhile, investment interest does not have a significant effect on sukuk demand, although most respondents demonstrate a relatively high level of interest. This suggests that portfolio preferences and other rational considerations are more dominant in determining investment decisions. From an Islamic economic perspective, demand is not only influenced by price and profit factors but also reflects ethical values, spirituality, and social responsibility in economic activities. Thus, this study confirms that rational economic factors and Islamic values play a role in shaping demand for government sukuk.